2021
DOI: 10.1021/acs.nanolett.1c04238
|View full text |Cite
|
Sign up to set email alerts
|

Facile Separator Modification Strategy for Trapping Soluble Polyphosphides and Enhancing the Electrochemical Performance of Phosphorus Anode

Abstract: Phosphorus anode is one of the most promising candidates for high-energy-density lithium-ion batteries. Recent studies found the lithiation process of phosphorus is accompanied by the soluble intermediates of lithium polyphosphides. The trans-separator diffusion of polyphosphides is responsible for the capacity decay. Herein, a facile separator modification strategy is proposed for improving the performance of phosphorus anode. The lightweight CNT-modified layer that has a continuous conductive skeleton, a den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…The binding energies (E b ) of polyphosphides (LiP 7 and LiP 5 ) [13,40] with Bi or LiBi were calculated by density functional theory, respectively, as shown in Figure 5h and Figure S20 (Supporting Information). Both Bi and LiBi offer high adsorption energy for LiP 7 and LiP 5 .…”
Section: The Role Of Bi In the Bi-p/c Anodementioning
confidence: 99%
“…The binding energies (E b ) of polyphosphides (LiP 7 and LiP 5 ) [13,40] with Bi or LiBi were calculated by density functional theory, respectively, as shown in Figure 5h and Figure S20 (Supporting Information). Both Bi and LiBi offer high adsorption energy for LiP 7 and LiP 5 .…”
Section: The Role Of Bi In the Bi-p/c Anodementioning
confidence: 99%
“…Therefore, new methods to enable efficient bonding of P and C need to be developed. Moreover, most recent research results have shown that the lithium polyphosphide intermediates may be soluble in electrolyte, [ 80 ] which may accelerate capacity fading upon cycling. Finally, the high P content also increases SEI generation, which affects both Li‐ion diffusion and electron conductivity.…”
Section: Phosphorus‐based Anodesmentioning
confidence: 99%
“…A direct approach is the application of other electrode materials with higher specific capacity in comparison to the current commercial LIB electrode, such as a manganese-rich layered oxide for the cathode as well as Si, Sn, and P for the anode, and many impressive results have been reported presently. Sun et al employed a lightweight CNT-modified layer to capture the soluble lithium polyphosphide, leading to a high specific capacity of 1505 mAh g –1 at 250 mA g –1 (200th cycle) and 1312 mAh g –1 at 2 A g –1 . Amine et al found that Mn substitution can effectively alleviate the destructive effects of Co and demonstrated a series of promising Co-free cathodes .…”
Section: Introductionmentioning
confidence: 99%